ANRIL rs2383207 polymorphism and coronary artery disease (CAD) risk: a meta-analysis with observational studies - Wang, P.; Dong, P.; Yang, X. (Cellular and Molecular Biology, 2016)
Some studies investigated the association of antisense non-coding RNA in the INK4 locus (ANRIL) rs2383207 polymorphism with coronary artery disease (CAD) risk. However, the result was still inconsistent. The aim of this study was to investigate whether there is an association between the ANRIL rs2383207 polymorphism and CAD risk. We carried out a PubMed (Medline), EMBASE database search covering all published articles. The strength of association between ANRIL rs2383207 polymorphism and CAD risk was assessed by calculating OR with 95% CI. A total of 13 case-control studies involving 6796 cases and 9956 controls were included in this meta-analysis. ANRIL rs2383207polymorphism was associated with a significantly an increased risk of CAD (OR=1.47; 95%CI, 1.33-1.62). We also found that this polymorphism increased CAD risk in Caucasians (OR=1.51; 95%CI, 1.28-1.77) and Asians (OR=1.42; 95%CI, 1.26-1.61). In the subgroup analysis according to gender, both women and men were significantly associated with the increased risk of CAD (OR=1.36; 95%CI, 1.03-1.79 and OR=1.58; 95%CI, 1.20-2.09). In the subgroup analysis by age, ANRIL rs2383207 polymorphism showed significant results in old CAD patients and young CAD patients (OR=1.32; 95%CI, 1.20-1.44 and OR=1.53; 95%CI, 1.32-1.77). Furthermore, this polymorphism also influenced myocardial infarction risk (OR=1.75; 95%CI, 1.24-2.47). Even the studies with adjustment for age, gender, smoking were included, the significant association was also observed (OR=1.43; 95%CI, 1.26-1.62). In conclusion, this meta-analysis suggested that ANRIL rs2383207 polymorphism is associated with CAD risk.